(untitled) (Research, Society and Development, 2020)
Objective: to check the existence of an association between personality traits of the caregiver of elderly people with dementia and family functionality. Method: cross-sectional study with the participation of 118 caregivers of elderly people with dementia in two geriatric services. The following variables were investigated: family functionality (family APGAR scale); sociodemographic; cognitive impairment of the elderly person (GDS scale); personality traits of the caregiver (NEO-FFI-R inventory); overload (Zarit overload inventory); depressive symptoms (CES-D scale). Beta regression and path modeling were used to check the hypothesis of the influence of these variables on family functionality. Results: Beta regression pointed to a predictive model in which the variables “do not share care”, “cognitive impairment of the elderly person”, “depressive symptoms of the caregiver” and “conscientiousness” have influence on family functionality. Path modeling showed that personality traits of caregivers have a strong influence on overload and depressive symptoms. Conclusion: The study contributed to highlighting the importance of enhancing the assistance to the caregiver of the elderly person with dementia. The results point to the need for intervention studies that consider the personality of the caregiver, the family support and the psychological health of the caregiver, aiming at the preparation of specific and more effective protocols.